Managing application integration capabilities - Jokinen, Annika (My University, 2021)
Majority of application integration projects fail to accomplish their goal. One of the main reasons for these failures is the lack of management and governance within the organization implementing the application integrations. Strategic and effective utilization of application integrations provides organizations with operational benefits by adding flexibility and reducing complexity of the information system landscape. Such advantages can be critical in current rapidly changing business environment. This thesis studies existing literature and research on application integration implementation and management and compares them with current practice of application integration work. Prior application integration research presents Enterprise Application Integration (EAI) as a prominent solution for organizations application integration problems. EAI is a mere technical solution but rather an organizational integration scenario or a connecting layer between business and technical layers. Few methodologies and frameworks for application integration implementation exist. Articles presenting these approaches have practical implications and recommendations for implementing and managing application integrations within an organization. They include lots of organizational and managerial aspects and observations. Specific frameworks or methodologies for application integration management on the organizational level were not found. An empirical study was carried out as a qualitative study by interviewing nine application integration professionals from five different software providers. Interviews considered three main themes: integration challenges, organizational integration capabilities and integration management. Respondents were asked to reflect their work experience and customer knowledge especially within application integration implementation projects. Most of the challenges and observations from the previous research were present in the results of this study. Management issues were seen having an impact for application integrations from the design phase until the maintenance phase. Five categories of general application integration management categories were presented to help outlining the complex and wide nature of application integration capability management.

Suurin osa ohjelmistojen integrointihankkeista ei saavuta tavoitteitaan. Yksi tärkeimmistä syistä näihin epäonnistumisiin on puutteellinen integraatiotyön johtaminen ja hallinta integraatiota toteuttavassa organisaatiossa. Ohjelmistointegraatioiden strateginen ja tehokas hyödyntäminen mahdollistaa organisaatioille toiminnallisia etuja lisäämällä joustavuutta ja vähentämällä tietojärjestelmien monimutkaisuutta. Tällaiset edut voivat olla kriittisiä nykyisessä nopeasti muuttuvassa liiketoimintaympäristössä. Tämä opinnäytetyö tutkii olemassa olevaa kirjallisuutta ja tutkimusta ohjelmistointegraatioiden toteuttamisesta ja hallinnasta sekä vertaa niitä tämänhetkisiin sovellusten integrointityökäytäntöihin. Aiemmat ohjelmistointegraatiotutkimukset erilaisia integraatioratkaisuja vastauksena organisaatioiden sovellusten integrointiongelmiin. Enterprise Application Integration eli EAI ei ole pelkkä tekninen ratkaisu, vaan pikemminkin integraatioskenaario tai yhdistävä kerros liiketoiminnan ja teknisten kerrosten välillä. Ohjelmistointegraatioiden toteuttamiseen on muutamia menetelmiä ja viitekehyksiä. Näitä lähestymistapoja kuvaavissa artikkeleissa on käytännön esimerkkejä ja suosituksia ohjelmistointegraatioiden toteuttamiseen ja hallintaan organisaatiossa. Ne sisältävät erityisesti organisaatioon ja johtamiseen keskittyviä näkökulmia ja havaintoja. Varsinaisia viitekehyksiä tai menetelmiä ohjelmistointegraatioiden johtamiseen organisaatiotasolla ei löytynyt. Empiirinen tutkimus tehtiin laadullisena tutkimuksena haastattelemalla yhdeksää ohjelmistointegraatiotyön ammattilaista viidestä eri ohjelmistotoimittajayrityksestä. Haastatteluissa käsiteltiin kolmea pääteemaa: integraatiohaasteet, organisaation integraatiokyvykkyyttä ja integraatioiden johtamista. Vastaajia pyydettiin pohtimaan työ- ja asiakaskokemuksiaan erityisesti ohjelmistointegraatioiden käyttöönottoprojekteissa. Suurin osa aiemman tutkimuksen haasteista ja havainnoista kävi ilmi myös tämän tutkimuksen tuloksista. Johtamiseen liittyvien ongelmien havaittiin vaikuttavan ohjelmistointegraatioiden käyttöönoton kaikissa vaiheissa, suunnitteluvaiheesta ylläpitovaiheeseen. Tutkimuksen tuloksena esitetään viisi yleistettävää ohjelmistointegraatioiden johtamisen kategoriaa, joiden tarkoituksena oli auttaa hahmottamaan ohjelmistointegraatiokyvykkyyden johtamisen monimutkaista ja organisaation laajuista luonnetta.
Keywords: application integration management, integration capability, enterprise application integration, enterprise integration methodology, application integration solution, application integration implementation